Frictional resistance of aesthetic brackets - Farah G Agha; Mushriq F Al-Janabi (College of Dentistry/ University of Baghdad, 2014)
Background: The aim of this study was to evaluate and compare the static frictional forces produced by monocrystalline ceramic (sapphire) bracket and polycrystalline ceramic bracket. Materials and methods: one hindered twenty brackets/segment of archwire combinations were used, each bracket/segment of archwire combination was tested 10 times. The tests were performed in a universal testing Instron machine. The data was submitted to in depended t-test. Results: The independent sample t-tests showed a highly significant difference in the static frictional forces between monocrystalline ceramic (sapphire) bracket and polycrystalline ceramic bracket. Conclusion: According to the biomechanical result gained from the present study, the monocrystalline ceramic (sapphire) brackets produced lower static friction level than polycrystalline ceramic bracket.